Indagini quantitative negli studi delle disabilità e dei DSA: problemi e prospettive in ambito nazionale e internazionale - Lucia Chiappetta Cajola (LED Edizioni Universitarie, 2014)
Quantitative Investigations in Studies on Disabilities and Specific Learning Disorders: National and International Problems and Prospects Gathering, organizing, describing and interpreting data are the steps which, in particular, characterize the quantitative investigation process. They are considered to have growing importance in a society where it is fundamental to fully comprehend the great and complex changes underway, in order to be able to effectively respond to the challenge of improving the quality of education for all students. Starting from this premise, this contribution aims to provide a picture of the quantitative investigations carried out at both national and international level within studies of disabilities and of specific learning disorders, and highlights the critical aspects linked to the many different survey tools and methods employed for obtaining data and information in various countries. This plethora of methods and tools does not make for having statistically comparable data to describe the problems hindering student learning and participation in school life, and to obtain the various trends. The article maintains that the efforts to empirically and operationally account for such a complex reality makes it necessary to enhance actions for integrating competencies with regard to the renewed and decisive support and also involvement of authoritative national and international bodies which can methodologically reorient investigation procedures by overcoming the critical aspects linked to the use of concepts, definitions and classifications as well as the criteria for data-gathering and database management, also bearing in mind the many actors involved and the relative legislative and normative constraints.